2010
DOI: 10.1590/s1413-70542010000600013
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento in vitro de mudas micropropagadas de bananeira (Musa sp.) em diferentes meios de cultivo

Abstract: RESUMOObjetivou-se, neste trabalho, avaliar o processo de enraizamento in vitro de mudas micropropagadas das cultivares de bananeira (Musa sp.) 'Nanicão Jangada' (AAA), 'Nanicão Grande Naine' (AAA) e 'Maçã' (AAB) utilizando-se os meios de cultivo semissólido e líquido. Foram utilizadas mudas micropropagadas oriundas de meristemas retirados de mudas do tipo chifrinho coletadas em bananais comerciais na Região do Médio Paranapanema, estado de São Paulo. Foram constituídos dois tratamentos sendo: meio líquido, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…A root presence was observed in all of the treatments (100%), regardless of the temperatures and the concentrations of the salts in the growth medium. The presence of roots may have indicated that the plants were developing satisfactorily and that the in vitro conditions did not limit the resumption of their growth (CAMOLESI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A root presence was observed in all of the treatments (100%), regardless of the temperatures and the concentrations of the salts in the growth medium. The presence of roots may have indicated that the plants were developing satisfactorily and that the in vitro conditions did not limit the resumption of their growth (CAMOLESI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…All the same, there were no significant differences in any of the treatments at both of the temperatures. The presence of roots may have indicated good growing conditions, being positive for the resumption of growth, whenever it was necessary and beneficial for the eventual acclimatization (CAMOlESI et al, 2010). Concerning the height, the plantlets showed little growth, as this was the main purpose of slow growth, regardless of the temperatures and the osmotic regulators (Table 2).…”
Section: Osmotic Regulators and The Cultivation Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…As cultivares de bananeira com frutas comestíveis são propagadas de forma vegetativa, quer seja a campo, a partir de brotações laterais, cujas taxas de multiplicação são baixas e contribui para a disseminação de pragas e doenças; ou em laboratório de micropropagação (Carvalho et al, 2012). Embora, a propagação in vitro seja a melhor opção e proporcione mudas sadias em larga escala e em pequeno espaço físico (Camolesi et al, 2010), o emprego de mudas produzidas por essa tecnologia é limitado devido ao alto custo de produção.…”
unclassified